Strategic framework for selecting advanced air defence systems: insights from a developing country: A Hybrid MCDM Framework for Missile Systems Selection - Ali, Yousaf (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/Purpose: In  this  modern  world,  every  country  is  trying  to  improve its defense system by acquiring new technologies. One of the main components of a defense system is the Air Defense System (ADS), which further includes fighter aircraft, drones, 3D radar, fighter command vehicles, and missile systems. The missile system has become the most important component  of  air  defense  systems  around  the  globe.  Due  to  the  limited  resources and weak economy, it is a challenge for a developing country to acquire  an  ADS  that  suits  its  resources  and  economic  capabilities.  This  research paper aims to study the needs and goals of the defense system of  the  Pakistan  Air  Force  (PAF)  and  to  select  the  best  missile  system  to  improve its existing air defense system.  Methods: A  hybrid  Multi-Criteria  Decision  Making  (MCDM)  methodology,  Decision-Making   Trial   and   Evaluation   Laboratory   (DEMATEL),   and Analytical  Hierarchy  Process  (AHP)  are  used  to  evaluate  the  factors  affecting the missile system as well as to select the best missile system for Pakistan. Results: The  results  depict  that  the  S-400  missile  system  is  the  most  feasible for Pakistan's air defense, followed by THAAD and S-300, which can meet the country's current security needs.Conclusion: The research concludes that precision target capability, range, and maneuverability are the prominent factors that play a greater role in the ADS  sector  of  Pakistan.  This  research  is  the  first  of  its  kind  to  use  the  DEMATEL-AHP approach for the evaluation of air defense systems in the case of a developing country such as Pakistan.
Keywords: Pakistan air defense system, Missile System, MCDM, DEMATEL-AHP